Civic Virtue dalam Pendidikan Kristen guna Memperkuat Etika Digital di Era 4.0 - Rahmelia, Silvia; Apandie, Chris (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2023)
Along with changes in citizens’ socio-cultural order due to disruption era in industrial revolution 4.0, civic virtue as a part of citizens’ character internalization needs to be strengthened in order to established digital ethics in the 4.0 era. It could be implemented through citizenship education in Higher Education, but also deemed necessary in Christian education through general way so that citizens well to continue to prioritize civic virtues/ethical responses as Christians. The purpose of internalizing civic virtue in Christian education to established digital ethics in the 4.0 era will discuss the following propositions civic virtue in the digital era (internet of things) and civic virtue in Christian education. This study uses library research. It is hoped that this thought construction could strengthen Indonesian citizens’ mindset on the praxis by the virtues from God. Thus, citizens can be consistent in implementing the principles of reason and values when dealing with all the challenges resulting from the sophistication of industrial technology 4.0. AbstrakSeiring dengan berubahnya tatanan sosial budaya warga negara akibat disrupsi di era revolusi industri 4.0, civic virtue sebagai bagian dari internalisasi karakter warga negara perlu diperkuat dalam penerapan etika digital di era 4.0. Penguatan dapat dilakukan tidak hanya melalui pendidikan kewarganegaraan di Perguruan Tinggi, namun juga dipandang perlu dalam pendidikan Kristen secara umum sehingga warga negara dapat tetap mengedepankan adab-adab kewarganegaraan sebagai umat Kristiani. Tujuan internalisasi civic virtue dalam pendidikan Kristen guna memperkuat penerapan etika digital di era 4.0 akan membahas proposisi civic virtue di era digital (internet of things) dan adab kewarganegaraan (civic virtue) dalam pendidikan Kristen. Kajian ini menggunakan studi kepustakaan. Diharapkan konstruksi pemikiran ini dapat memperkuat pola pikir warga negara Indonesia pada praksis nilai-nilai kebajikan yang berasal dari Tuhan. Dengan demikian, warga negara dapat konsisten dalam mengimplementasikan prinsip nalar dan nilai ketika berhadapan dengan segala tantangan yang dihasilkan dari kecanggihan teknologi industri 4.0.